SEDIMENTOLOGY OF A MUDDY ALLUVIAL DEPOSIT: TRIASSIC DENWA FORMATION, INDIA - Ghosh P.; Sarkar S.; Maulik P. (My University, 2006)
Triassic Upper Denwa Formation (~ 380 m) in the Satpura Gondwana basin, central India is a mudstone-dominated fluvial succession that comprises isolated ribbon-shaped (2-5-m-thick) channel-fill bodies encased within fine-grained extra-channel deposits. Eight architectural elements are recognized, of which five belong to channel-fill deposits and the remaining three to extra-channel deposits. Majority of channel-fill deposits are characterized by sandy or muddy inclined heterolithic strata (IHS) that record limited lateral accretion of point bars or benches (constrained by cohesive banks) in mixed- to suspended-load sinuous channels. A few ribbon bodies are mud rich and attest to nearly stagnant conditions in partly abandoned channels. A few single- or multistorey ribbon bodies that are dominantly sandy and lack inclined strata represent deposits of straight, laterally stable channel. The smallest ribbon bodies (~ 1 m thick) of calcirudite/calcarenite possibly represent deposits of secondary channels in the interfluves. Coexistence of channel-fill bodies of different dimension, lithology and internal organization in restricted stratigraphic intervals suggests an anabranching system having channels with different fill histories. The extra-channel deposits mainly comprise red mudstone (1-5 m thick) that indicates pervasive oxidation of overbank sediments in well-aerated and well-drained setting. Sporadically developed calcic vertisols suggest a hot, semi-arid climate during the Upper Denwa period. Sandy to heterolithic sheets (70 cm to 2 m thick) with sharp, planar basal surfaces are replete with features suggestive of unconfined sheet flow. Also at places there are indications of subaqueous emplacement of sands. These bodies with paleocurrent oblique to that of the channel-fills are interpreted as crevasse splay deposits. Tabular heterolithic bodies (3-5 m thick) are characterized by undulating basal surface, complex organization of sandstone lenses interwoven with heteroliths and red mudstone (in decimeter-scale) with desiccation cracks. Such tabular bodies are attributed to repetitive, sheet-like and poorly channelized splaying. Very thick (10 to 20 m) mudstones intervals are inexplicable in terms of overbank flooding only. Poorly developed pedogenic features in sandy to muddy heterolithic sheets and certain mudstone intervals and well-developed cumulative paleosols in surrounding mudstone highlights the contrast between rapidly emplaced splay deposits and slowly accumulated floodplain deposits. The Denwa channels are comparable with modern, low-gradient and low-energy anabranching river system in which the sediment load is dominantly fine-grained. The semi-arid climate possibly facilitated enhanced supply of fines to the Upper Denwa system. However, sediment partitioning and distribution in a particular channel was controlled by flow diversion to and from other channels in that anabranching system. Low flow strength with periodic flood events, high bank strength and a rate of sediment supply that slightly exceeded that of onward transport probably were important factors for the development of the Upper Denwa anabranching system. © 2006 Elsevier B.V. All rights reserved.
Keywords: FLUVIAL; HETEROLITHS; MIXED-LOAD TO SUSPENDED-LOAD RIVERS; MUDSTONE; SEMI-ARID; SPLAY; Triassic; Mesozoic::Triassic; Мезозой::Триасовая